AutoLock: a semiautomated system for radiotherapy treatment plan quality control. (8th May 2015) - Dewhurst, Joseph M.; Lowe, Matthew; Hardy, Mark J.; Boylan, Christopher J.; Whitehurst, Philip; Rowbottom, Carl G.
Abstract : A semiautomated system for radiotherapy treatment plan quality control (QC), named AutoLock, is presented. AutoLock is designed to augment treatment plan QC by automatically checking aspects of treatment plans that are well suited to computational evaluation, whilst summarizing more subjective aspects in the form of a checklist. The treatment plan must pass all automated checks and all checklist items must be acknowledged by the planner as correct before the plan is finalized. Thus AutoLock uniquely integrates automated treatment plan QC, an electronic checklist, and plan finalization. In addition to reducing the potential for the propagation of errors, the integration of AutoLock into the plan finalization workflow has improved efficiency at our center. Detailed audit data are presented, demonstrating that the treatment plan QC rejection rate fell by around a third following the clinical introduction of AutoLock. PACS number: 87.55.Qr